2016
DOI: 10.1007/s10029-016-1525-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostheses size dependency of the mechanical response of the herniated human abdomen

Abstract: Our findings suggest that the anisotropy of the mesh becomes more relevant with the increase of the defect size. Additionally, according to our results Optilene showed the closest deformation to the natural distensibility of the abdomen while Infinit should be carefully used due to its excessive compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this respect, our group has made contributions in the field of biomechanics showing that PP-LW meshes such as Optilene [ 30 ] displayed a mechanical response similar to healthy muscle. Numerical simulations models of reconstructed herniated human abdominal wall based on abdomen geometry obtained by magnetic resonance imaging support this theory, as they have shown that these LW meshes showed the closest deformation to the natural distensibility of the abdomen [ 33 ]. Optimal clinical results in abdominal hernia repair strongly depend on a perfect match between the mechanical properties of the abdominal wall and those of the biomaterial used for repair in the long term [ 34 ].…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, our group has made contributions in the field of biomechanics showing that PP-LW meshes such as Optilene [ 30 ] displayed a mechanical response similar to healthy muscle. Numerical simulations models of reconstructed herniated human abdominal wall based on abdomen geometry obtained by magnetic resonance imaging support this theory, as they have shown that these LW meshes showed the closest deformation to the natural distensibility of the abdomen [ 33 ]. Optimal clinical results in abdominal hernia repair strongly depend on a perfect match between the mechanical properties of the abdominal wall and those of the biomaterial used for repair in the long term [ 34 ].…”
Section: Discussionmentioning
confidence: 96%
“…Thus the mechanical behaviour of surgical meshes and abdominal tissues has been studied and reported in literature (see extensive review of Deeken and Lake, 2017). Compatibility between an implant and an abdominal wall can be assessed experimentally (Junge et al, 2001;Anurov et al, 2012) according to various criteria (Maurer et al, 2014) or by computer simulations (Simón-Allué et al, 2016;Todros et al, 2018;He et al, 2020). The computational approach allows for in silico testing of various cases and empowers optimisation of ventral hernia treatment (Szymczak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%